Highly graphitized 3D network carbon for shape-stabilized composite PCMs with superior thermal energy harvesting. (July 2018) - Chen, Xiao; Gao, Hongyi; Yang, Mu; Dong, Wenjun; Huang, Xiubing; Li, Ang; Dong, Cheng; Wang, Ge
Abstract: One major barrier obstructing their scale engineered adoption of phase change materials (PCMs), currently, is their low thermal conductivity, which drastically constrains the power capacity. Our target is to enhance the PCMs thermal conductivity without evidently altering other thermal property criteria. Herein, we propose a facile, low-cost and controllable strategy to construct compactly interconnected 3D celosia-like highly graphitized thermally conductive network carbon via carbon quantum dots (CQDs) deriving from acetone and divinyl benzene (DVB). Novel function of CQDs is firstly developed for superior thermal energy harvesting, thus expanding their conventional fluorescence and catalysis field to novel thermal energy storage. Importantly, our constructed 3D graphitized network carbon better infiltrates macromolecule polyethylene glycol (PEG) and fully releases crystallization via controllable crosslinking reaction. This strategy simultaneously integrates sufficient power capacity and incremental thermal conductivity (enhanced by 236%) of the PCMs, and thermal enthalpy is considerably approaching the theoretical value. Alternatively, the composite PCMs are thermally and durably stable. These results indicate that resulting shape-stabilized PCMs are a very promising candidate for renewable thermal energy storage in virtue of the superior comprehensive properties. Graphical abstract: Schematic illustration of PEG8000 @ CQDs-derived 3D porous carbon composite PCMsfx1 Highlights: Novelty function of carbon quantum dots is firstly developed for superior thermal energy storage. 3D highly graphitic compact carbon network is successfully prepared for providing superior interconnected path for phonon propagation. Pore structures of 3D highly graphitic carbon network are effectively regulated via divinyl benzene and calcination temperature. The obtained PCMs greatly enhance thermal conductivity without evidently reducing other thermal criteria.